Developing a Social Media Marketing Plan for Kojine Vietnam Brand of Binh Phu Trading & Service Co., Ltd - Pham, Thi Thanh Quyen (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Business Administration; 2021-2025